(untitled) (Research, Society and Development, 2021)
This article aims to verify the coping strategies used by health workers in view of the demand for welcoming users in a psychosocial care center. This is a descriptive cross-sectional study with a sample of 14 professionals from a Psychosocial Care Center located in the city of Rio de Janeiro (RJ) in 2019, who answered sociodemographic and occupational questions and the Occupational Coping Scale. In the treatment of the data, we worked with descriptive statistical analysis. In the results, it is possible to observe that the sample was composed mainly of females, singles and age group between 25 and 34, outsourced employment and only one source of income. Among the factors and respective coping strategies used frequently and always, the control factor was mostly identified through actions aimed at problem solving and social support followed by the symptom management factor, mainly outside the occupational environment through leisure activities, physical exercise and change in eating habits. Regarding avoidance strategies, which are not very significant in the sample, it was identified that workers resort to emotion regulation in order to minimize occupational stress. It is concluded that the prevalence of strategies centered on the control and management of symptoms in the sample shows occupational stress and health risks for workers.